Ethanol extract of Bruguiera gymnorrhiza mangrove leaves and propolis activity on macroscopic healing of cuts in vivo - Evi Kurniawaty; Shina Megaputri; Syazili Mustofa; Soraya Rahmanisa; Kholis Abdurachim Audah; Silvia Andriani (Acta Biochimica Indonesiana, 2022)
Background: Bruguiera gymnorrhiza mangrove and propolis are often used as natural wound treatments. Its constituent is believed to promote wound healing. Objective: This study aims to explore the effect of topical administration of ethanol extract of Bruguiera gymnorrhiza mangrove leaves and propolis on wound healing activity. Methods: Twenty-four Sprague Dawley rats were randomly assigned to one of four treatment groups (n=6): aqua dest, standard wound medicine, ethanol extract of Bruguiera gymnorrhiza mangrove leaves, and propolis extract. Following the incision, treatment was given once a day for 14 days or until the wound healed. The cut area was observed by measuring the cut length using a ruler. Results: Standard wound medication took 9 days to promote healing, while the negative control (aqua dest) took 11.2 days, the ethanol extract of Bruguiera gymnorrhiza mangrove leaves took 7.3 days, and the propolis extract took 7.9 days. Conclusions: Topical administration of Bruguiera gymnorrhiza mangrove leaves ethanol extract and propolis had equal effects on the healing of wounds. Both are more effective than conventional wound ointments at healing cuts.